Nature Of Science (NOS) Learning Module Development Oriented to Improve Students Scientific Literacy - Rambe, Titin Rahmayanti; Lubis, Renni Ramadhani; Purba, Azrina; Parinduri, Wina Mariana; Saputra, Andri (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
This research is research and development (R&D). The object of research is the science learning module containing Nature of Science (NOS). This research is a Four-D model. This development model consists of four stages, namely the define, design, develop, and disseminate stages. The research instrument used in the study was a validation sheet by 3 experts (language expert, material expert, media expert), and 1 teacher and student responses. The results of the validation test results by experts are linguists (87.36), material experts (86.99), and media experts (88.52%), and teacher expert validation (88.23%). The results of the small group trial with the pretest of 44.44% and the posttest reaching 77.8%, the results of the medium group trial with the percentage of scientific literacy of students at the pretest by 50% and at the posttest reaching 77.78% and the results of the large group trial with the percentage of scientific literacy of students at the pretest of 38.59% and at the posttest reaching 80.35%. Based on this percentage, the science learning module containing the nature of science (NOS) which is oriented to improving students' scientific literacy is effective to use. Student responses to the module with a percentage of 87.26%.